Effects of Temperature on Competition Between Toxic and Non-Toxic Raphidiopsis raciborskii and Cylindrospermopsin Production - Wei Liu; Xin Tang; Sainan Zhang; Mingting Lei; Lamei Lei (Diversity)
Toxic and non-toxic strains of Raphidiopsis raciborskii coexist widely in natural water bodies, with the dominance of toxic strains directly influencing bloom toxicity. This study investigates how temperature affects the relative dominance of toxic R. raciborskii strains and the production of cylindrospermopsin (CYN). We conducted monoculture and co-culture experiments in nutrient-rich BG11 medium at three temperatures (16 °C, 24 °C, and 32 °C) using two pairs of strains (CS506/CS510 from Australia and QDH7/N8 from China). The results revealed that the Australian strains failed to grow at 16 °C, while the Chinese strains thrived. In a co-culture experiment, the Australian toxic strain CS506 exhibited the fastest growth at 24 °C, whereas the Chinese toxic strain QDH7 reached similar maximum cell densities across all temperatures but peaked more quickly at 24 °C and 32 °C compared to 16 °C. Regardless of temperature and strain pairs, toxic strains consistently maintained a higher relative abundance than their non-toxic counterparts. Analysis using the rate of competitive displacement (RCD) model indicated that higher temperatures accelerated the displacement of non-toxic strains by toxic ones. Total CYN concentrations in co-cultures increased with temperature, although the cell quota of CYN (QCYN) did not vary significantly across temperatures. In co-culture, the CYN production rate during the exponential phase was positively correlated with cell growth rate, but this correlation weakened or reversed in the stationary phase, likely due to changes in nutrient availability. These findings suggest that rising temperatures under eutrophic conditions may enhance the growth and competitive advantage of toxic R. raciborskii strains, thereby exacerbating bloom toxicity.